Strategic Innovation Model for Business Resilience: A Case Study of PT Zenna Home Living - Hosannah, Matthew Terrence Amadeus; Ratnaningtyas, Sudrajati (Journal of Applied Business, Taxation and Economics Research, 2025)
This research addresses the challenge of sustaining growth in a founder-led SME within the Indonesian home living industry. It focuses on PT Zenna Home Living, a company facing inconsistent growth and operational inefficiencies despite its initial success, indicating a significant gap between its strategic vision and internal capabilities. The primary objective is to diagnose the root causes of this gap and propose a practical model to enhance the company's long-term business resilience. This study employs a qualitative, single case study methodology. Primary data was gathered through in-depth, semi-structured interviews with key informants selected purposefully from three organizational levels—Strategic, Managerial, and Operational. The data was systematically analyzed using thematic analysis, facilitated by NVivo software and guided by the Dynamic Capabilities framework. The results reveal three core strategic gaps: a "Sensing Gap" where the company is insight-rich but data-poor; a "Seizing Gap" or "visionary bottleneck" due to a highly centralized decision-making structure; and a "Transforming Gap" characterized by systemic barriers and a lack of standardized processes (SOPs). To address these gaps, this research proposes the "Zenna Adaptive Resilience Model," a holistic framework built on three pillars: (1) Systemic Digitalization (implementing a WMS); (2) Process Standardization (creating SOPs); and (3) Structured Empowerment (establishing an Innovation Council). The main contribution is a practical, evidence-based model that provides a clear roadmap for Zenna and similar SMEs to build a scalable operational foundation and shift from a personality-dependent to a system-driven organization, thereby achieving sustainable business resilience.